Bibliometric analysis and initial animal efficacy evaluation of top ten scoring drugs to enhance oral rehydration therapy in early post-burn shock - Liu, Xiang-Yu; Wu, Yu-Shou; Qu, Yi-Rui; Zhou, Hui; Liu, Tian; Su, Xiao-Wei; Hu, Fang-Chao; Zheng, Jin-Guang; Han, Shao-Fang; Chai, Jia-Ke; Chi, Yun-Fei (Frontiers in Pharmacology, 2025)
Background/objectivesBurns can cause severe physiological disturbances. Oral rehydration therapy (ORT) is an alternative to intravenous fluids. However, the World Health Organization-recommended oral rehydration solution (WHO-ORS) lacks specific components to address the critical physiological changes in patients with burns. This study aimed to identify and evaluate several drugs that enhance the ORT efficacy in burn shock management.MethodsA systematic search of PubMed, Web of Science, and Scopus (2000.01.01–2024.06.30) yielded 1,500 relevant studies, from which 270 were selected for bibliometric analysis. Drug candidates (≥3 mentions) were prioritized via the Bibliometric Evidence Score (BES) integrating publication frequency, journal impact factor (5-year average), impact score, and Q1 journal distribution. Subsequently, the translational potential of these candidates was assessed using an Integrated Translational Score incorporating weighted dimensions: Mechanistic Clinical Alignment Score (weight = 0.45), Emergency Deployment Feasibility (weight = 0.20), and BES (weight = 0.35). The top 10 drugs by the BES were selected for experimental validation, which were tested in a rat model with 50% total body surface area full-thickness burns (n = 286, 22/group), comparing sham controls, untreated controls, WHO-ORS, and drug-adjuvanted ORS groups. Primary outcomes included 48 h survival rate and blood lactate (Lac), hematocrit (HCT), malondialdehyde (MDA), and interleukin-6 (IL-6) levels.ResultsTeprenone or vitamin C in combination with the WHO-ORS significantly improved survival outcomes following severe burns. They reduced blood lactate, HCT, MDA, and IL-6 levels. Glutamine and ethyl pyruvate showed beneficial effects but did not significantly improve survival. Hypertonic Saline and Dobutamine failed to demonstrate efficacy.ConclusionThis study demonstrated that adding teprenone or vitamin C to the WHO-recommended ORS can enhance the therapeutic efficacy of ORT in managing burn shock. These findings provide a scientific basis for further clinical trials and development of optimized ORS for patients with burns.